Eco-Feminism in Contemporary Female Iranian Poetry - Bagheri, Narges; Hamidi, Shahrouz (European Journal of Multidisciplinary Studies, 2016)
Today, nature, land and environment are of the important issues that everyone in his/her own position could have an important role in protecting them. Eco-feminism is a branch of feminism that communicates between ecology and feminism. Generally speaking, it can be said that Eco-feminists stesses on the three similar issues: women’s relationships with nature, the relationship between domination over women and domination over nature, the role of women in solving ecological problems. One of their main arguments is that women mainly damage more from environmental pollution in comparison to men, as a result, the environment issue is mainly a gender-related issue. There is a consensus on the moral issues of environment protection, which is based on the wemen’s work and social posion, among eco-femenists. But their strategies for a change are different. One of these strategies is cultural strategy and can be related to literature and poetry. This paper explores the contemporary women’s poetry from this point of view. Many of contemporary Iranian poetry samples show that they are closely linked with the nature. Respecting to the nature and environmental concerns and the preservation of nature has been reflected in their poetry and this voice can help changing the thought of society.